2019
DOI: 10.1111/ajco.13123
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative C‐reactive protein to albumin ratio is a predictor of survival after pancreatic resection for pancreatic ductal adenocarcinoma

Abstract: AimSystemic inflammation and nutritional status are associated with clinical outcomes of cancer patients. We investigated the prognostic value of preoperative C‐reactive protein to albumin ratio (CAR) in patients with pancreatic ductal adenocarcinoma (PDA) after pancreatic resection.MethodsOne‐hundred and thirty‐six PDA patients who underwent pancreatic resection between January 2005 and June 2017 were retrospectively enrolled. Preoperative inflammation‐based scores including CAR, modified Glasgow prognostic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…Patients with a CAR >0.03 showed a shorter disease-free survival and a decreased survival time in our study population. Compared to Wu et al (19) and Haruki et al (12) this cut-off value seems small, but with the correct conversion factor from mg/l (CRP) to g/dl (albumin) and an average CRP of 15 Ikuta et al (13) have reported greater difference in median overall survival time in patients with higher and lower CAR Kaplan-Meier analysis of our cohort, indicated that CRP and albumin alone were not associated with worse outcome (a: p=0.091, b: p=0.103). According to this, serum levels of CRP alone did not correlate with overall survival in univariate Cox regression analysis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Patients with a CAR >0.03 showed a shorter disease-free survival and a decreased survival time in our study population. Compared to Wu et al (19) and Haruki et al (12) this cut-off value seems small, but with the correct conversion factor from mg/l (CRP) to g/dl (albumin) and an average CRP of 15 Ikuta et al (13) have reported greater difference in median overall survival time in patients with higher and lower CAR Kaplan-Meier analysis of our cohort, indicated that CRP and albumin alone were not associated with worse outcome (a: p=0.091, b: p=0.103). According to this, serum levels of CRP alone did not correlate with overall survival in univariate Cox regression analysis.…”
Section: Discussionmentioning
confidence: 89%
“…CRP is synthesized by hepatocytes and its production is stimulated by proinflammatory cytokines, especially interleukin 6. Research states that inflammatory processes within the tumor activate systematic inflammatory pathways which are detectable and could be related to tumor prognosis and outcome (13,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The CAR has been described as a strong predictive factor for overall survival of other tumor types, such as intrahepatic cholangiocarcinoma, liver, lung and gastric cancer (10,18,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ikuta et al indicated that in 136 PDAC patients, preoperative CAR was an independent poor OS predictor using multivariate analysis. Moreover, the prognostic evaluation power of CAR was significantly higher than other inflammation-based factors such as NLR, platelet to lymphocyte ratio (PLR), and lymphocyte to monocyte ratio (LMR) (77). Besides, the study by Arima et al also confirmed this result through using CAR at day 14 after an operation (78).…”
Section: Comparison With Other Studies and Possible Explanationsmentioning
confidence: 90%
“…Ultimately, 20 studies [8,[15][16][17][18][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] including 6512 patients were enrolled in this meta-analysis after excluding ineligible studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%